Rheumatology - Klippel, John H.; Dieppe, Paul A. (London: Mosby, 1998)
(Producer) CD-ROM (version 2.0) presents over 2500 superbly-rendered full-color photographs, radiographs and illustrations fully integrated with all 1920 pages from the second edition of the parent text. The CD-ROM includes practical and effective on-screen tools and a highly intuitive navigation system to create an outstanding diagnostic and teaching resources.
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: Mac; Power Mac or 68040; 8MB RAM; system 7.0 or above; double-speed or faster CD-ROM drive;4MB available hard disc space.
System requirements: Win; minimum of 66MHz 486DX; double-speed or faster CD-ROM drive, VGA display; Windows 3.x or Windows 95; 4MB available hard disc space; a minimum of 8MB of RAM is recommended.
This program will run on systems with 8-bit color (256 colors) but for optimum performence 16-bit (thousands of colors) is strongly recommended.
Keywords: Musculosketal Disease -- software